Action taken by the Prevention and Occupational Risks Service against Monkeypox (Medicina y Seguridad del Trabajo, 2024)
Introduction: Monkeypox (MPX) is a viral disease responsible for self-limiting skin lesions. Person-to-person transmission is rare and occurs through respiratory droplets or contact with skin lesions. On 23rd July 2022, the World Health Organisation (WHO) declared an international public health emergency following the appearance of increasing numbers of cases not linked to endemic countries. Spain was one of the most affected countries.Method: Creation of an online form accessible via QR code to collect information on workers who were in contact with a suspected case of MPX. If confirmed, the Prevention and Occupational Risks Service will use the provided data to assess exposed workers, contact close contacts, indicate the actions to be adopted and carry out follow-up. In the case of a high-risk contact, Public Health will be contacted to initiate the recommendations implemented.Results: 34 source cases were detected, 25 confirmed, and data was received from 121 contacts: 1 high-risk, 11 low-risk and 99 non-risk. Conclusions: When a worker is suspected of MPX infection, multidisciplinary management is required by the emergency services, dermatology, preventive medicine, infectious diseases, microbiology and the SPRL. The SPRL is responsible for initiating the contact study and notifying the concessionary company. The use of an online form to collect information regarding workers who were in contact with a suspected case helps to make the contact investigation more efficient and effective.
Keywords: occupational medicine; mpox (monkeypox); data collection